2016
DOI: 10.1038/srep34595
|View full text |Cite
|
Sign up to set email alerts
|

GlycoMinestruct: a new bioinformatics tool for highly accurate mapping of the human N-linked and O-linked glycoproteomes by incorporating structural features

Abstract: Glycosylation plays an important role in cell-cell adhesion, ligand-binding and subcellular recognition. Current approaches for predicting protein glycosylation are primarily based on sequence-derived features, while little work has been done to systematically assess the importance of structural features to glycosylation prediction. Here, we propose a novel bioinformatics method called GlycoMinestruct(http://glycomine.erc.monash.edu/Lab/GlycoMine_Struct/) for improved prediction of human N- and O-linked glycos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 90 publications
1
44
0
Order By: Relevance
“…Numerous studies have suggested that a high-quality, wellestablished data set is crucial for training a robust and reliable prediction model of protease cleavage sites [37,[43][44][45]. In this study, we constructed a well-prepared benchmark data set for assessing the predictive performance of our method and other existing methods.…”
Section: Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have suggested that a high-quality, wellestablished data set is crucial for training a robust and reliable prediction model of protease cleavage sites [37,[43][44][45]. In this study, we constructed a well-prepared benchmark data set for assessing the predictive performance of our method and other existing methods.…”
Section: Data Setsmentioning
confidence: 99%
“…To improve the feature representation ability and identify a subset of optimal features that contribute the most to the prediction of substrate cleavage sites, we used a two-step feature selection strategy, which combined mRMR [42] with forward feature selection (FFS) as described in our previous work [30,44,45,94].…”
Section: Feature Selectionmentioning
confidence: 99%
“…Previous studies have shown that 3D structure-based features play an important role in improving the predictive performance of PTM sites [38,50]. Therefore, we calculated two commonly used protein 3D structure features, secondary structure features and solvent accessible area features by using DSSP [42] and NACCESS [43], respectively.…”
Section: D Structure-based Features Calculationmentioning
confidence: 99%
“…Since solvent accessible area (ASA) has been widely used in many bioinformatics fields, including hot spots identification [51], catalytic sites prediction [52], and glycosylation sites prediction [38]…”
Section: Solvent Accessible Area (Asa) Featuresmentioning
confidence: 99%
See 1 more Smart Citation